IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS ARTICULATE STORYLANE UNTUK MENINGKATKAN MOTIVASI BELAJAR - Eka selvia, Devi sela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study shows that the process of learning Aqidah-Akhlak is still dominated by conventional methods and minimal use of learning media. This has an impact on the low learning motivation of students. Therefore, innovation is needed through the implementation of Articulate Storyline media, which not only presents material in an interesting way but also encourages active student engagement. This study aims to evaluate the application of Articulate Storyline-based learning media in improving students' learning motivation in the Akidah-Akhlak subject at MTSS Al-Hikmah Bandar Lampung. The study employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The results indicate that the use of Articulate Storylane creates a more interactive and enjoyable learning experience, thereby increasing students' active participation and understanding of the material. Based on the data, 52% of students demonstrated very high learning motivation, while only 2% were in the very low category. Despite technical challenges such as limited facilities and teacher readiness, this media has proven effective in enhancing learning motivation and the quality of Akidah-Akhlak education.